Incidence of endophthalmitis after intravitreal application of anti VEGF therapy at the University Clinical Center in Tuzla, Bosnia and Herzegovina - Svjetlana Terzić; Adisa Pilavdžić; Amra Nadarević Vodenčarević (Medicinski glasnik, 2015)
Aim: To report the incidence of endophthalmitis following the use of intravitreal injection of anti- vascular endothelial growth factor (anti VEGF) therapy. Methods: In this retrospective study a total of 986 intravitreal bevacizumab injections were applied between January 2008 and April 2015 at the University Clinical Center Tuzla, Bosnia and Herzegovina (B&H). Since January 2012, a total of 55 intravitreal ranibizumab injections were applied and since October 2014, 60 intravitreal aflibercept injections were applied to patients. Results: Two cases of endophthalmitis following intravitreal injection of bevaciuzumab occurred and none after ranibizumab or aflibercept. The overall incidence of clinical endophtahlmitis was 0.2%. Conclusion: The results suggest that a low rate of endophthalmitis can be achieved by means of a protocol. This is a very important study as it is the first of this kind in B&H that documents the incidence of endophthalmitis after intravitreal application. Currently, bevacizumab in B&H is most frequently used intravitreal anti-vascular endothelial growth factor due to very low price.
Keywords: bevacizumab; aflibercept; ranibizumab; complications of intravitreal application